The power of place: teachers’ perception on effective professional development - Jacobs, Gwendolen Susanne (Kansas State University, 2022)
Professional development provides opportunities for teachers to acquire the knowledge needed to become experts in their classroom content and to improve their instructional skills to meet the needs of today’s student learners. While districts and curriculum leaders work to improve professional development design, teachers’ dissatisfaction with current professional development practices are still problematic. Teachers continue to find it ineffective, irrelevant, making them feel undervalued as professionals. This is evident in the rural educational setting. Rural educators need on-going, flexible, and job-embedded effective professional development to meet the specific needs of rural educators and their students. While few studies have examined teacher perception on professional development, even fewer studies focused on the rural place. This study provides educational leaders with a teacher’s perspective on what effective professional development looks and feels like for rural educators. Using narrative analysis of five rural educators’ interviews and drawing on Gruenewald's Critical Pedagogy of Place, this study sought to understand the experiences of five rural educators as they explored their personal histories, perceptions, and experiences in receiving effective professional development. The study is driven by three research questions to determine if teachers’ perceptions of effective professional development is influenced by their own sense of place and how they identify within that place. These questions included the following: 1. How do teachers in a rural setting perceive building and district level professional development? 2. In what ways does sense of place inform teachers’ perceptions of effective professional development? 3. In what ways do these perceptions inform teachers' decisions to act on their new learning? The key themes revealed participants acknowledged the challenges districts face when providing effective professional development and that it is most beneficial when connected to their specific needs. Most participants acknowledged the complexity of rural relationships and recognized how their personal histories and experiences helped make and enrich these relationships. The findings relative to the five participants’ experiences and their stories also suggest rural teachers do not fully recognize the extent by which their own sense of place and place identity influenced their perceptions on their learning. This can have several implications for district leaders, professional development directors and for current and future rural educators. If district leaders and professional development directors want to see implementation of teacher learning in the classroom, providing purposeful professional development must not only address the specific needs of rural educators and their students but also consider what teachers bring to the rural context in relationship to their professional learning.
Keywords: Professional development; Rural; Teacher perceptions; Rural place